Troponin elevation in acute ischemic stroke (TRELAS) - protocol of a prospective observational trial - Scheitz Jan F; Mochmann Hans-Christian; Nolte Christian H; Haeusler Karl G; Audebert Heinrich J; Heuschmann Peter U; Laufs Ulrich; Witzenbichler Bernhard; Schultheiss Heinz-Peter; Endres Matthias (BMC Neurology, 2011)
Abstract Background Levels of the cardiac muscle regulatory protein troponin T (cTnT) are frequently elevated in patients with acute ischemic stroke and elevated cTnT predicts poor outcome and mortality. The pathomechanism of troponin release may relate to co-morbid coronary artery disease and myocardial ischemia or, alternatively, to neurogenic cardiac damage due to autonomic activation after acute ischemic stroke. Therefore, there is uncertainty about how acute ischemic stroke patients with increased cTnT levels should be managed regarding diagnostic and therapeutic workup. Methods/Design The primary objective of the prospective observational trial TRELAS (TRoponin ELevation in Acute ischemic Stroke) is to investigate the frequency and underlying pathomechanism of cTnT elevation in acute ischemic stroke patients in order to give guidance for clinical practice. All consecutive patients with acute ischemic stroke admitted within 72 hours after symptom onset to the Department of Neurology at the Campus Benjamin Franklin of the University Hospital Charité will be screened for cTnT elevations (i.e. >= 0.05 μg/l) on admission and again on the following day. Patients with increased cTnT will undergo coronary angiography within 72 hours. Diagnostic findings of coronary angiograms will be compared with age- and gender-matched patients presenting with Non-ST-Elevation myocardial infarction to the Department of Cardiology. The primary endpoint of the study will be the occurrence of culprit lesions in the coronary angiogram indicating underlying co-morbid obstructive coronary artery disease. Secondary endpoints will be the localization of stroke in the cerebral imaging and left ventriculographic findings of wall motion abnormalities suggestive of stroke-induced global cardiac dysfunction. Discussion TRELAS will prospectively determine the frequency and possible etiology of troponin elevation in a large cohort of ischemic stroke patients. The findings are expected to contribute to clarify pathophysiologic concepts of co-morbid cardiac damage in ischemic stroke patients and also to provide a basis for clinical recommendations for cardiac workup of such patients. Trial registration clinicaltrials.gov NCT01263964